2021
DOI: 10.3390/en14196293
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Use of Sewage Sludge as a Threat of Microplastic (MP) Spread in the Environment and the Role of Governance

Abstract: Sewage sludge from wastewater treatment plants is commonly used as a soil amendment on agricultural land. Unfortunately, more and more research indicates that large amounts of microplastic (MP) are re-introduced to soil with sludge. This study aims to present the impact MP has on soil ecosystems, global trends in agricultural sludge management resulting from a high concentration of micropollutants in sludge, and finally propose a high-level strategy for sustainable sludge management. This strategy is mostly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…EU countries have recognized sewage sludge (SS) as a major factor contributing to the contamination of agricultural land, and this has led it to formulate high-level strategy for sustainable SS management by its member countries. The strategy involves multiple stakeholders being expected to work harmoniously to achieve the desired goal of appropriate and efficient management [ 58 ]. It requires a review of directive 86/278/EEC on SS that will recognize the relationship between sewage and MPs, as well strictly prohibiting SS disposal on land unless necessary.…”
Section: Efforts and Control Measures On A Global Scale By Internatio...mentioning
confidence: 99%
See 1 more Smart Citation
“…EU countries have recognized sewage sludge (SS) as a major factor contributing to the contamination of agricultural land, and this has led it to formulate high-level strategy for sustainable SS management by its member countries. The strategy involves multiple stakeholders being expected to work harmoniously to achieve the desired goal of appropriate and efficient management [ 58 ]. It requires a review of directive 86/278/EEC on SS that will recognize the relationship between sewage and MPs, as well strictly prohibiting SS disposal on land unless necessary.…”
Section: Efforts and Control Measures On A Global Scale By Internatio...mentioning
confidence: 99%
“…It requires a review of directive 86/278/EEC on SS that will recognize the relationship between sewage and MPs, as well strictly prohibiting SS disposal on land unless necessary. Additionally, it requires plans to actualize a circular economy and provide alternatives to SS handling through high tech processes in waste water sewage plant to be strengthened by research and development [ 58 ].…”
Section: Efforts and Control Measures On A Global Scale By Internatio...mentioning
confidence: 99%
“…Agricultural application is also limited by the permissible limits on heavy metal content, i.e., 20 mg/kgdry of Cd, 1000 mg/kgdry of Cu, 16 mg/kgdry of Hg, 300 mg/kgdry of Ni, 750 mg/kgdry of Pb, and 2500 mg/kgdry of Zn, as specified in European Council Directive 86/278/EEC [30]. For agricultural use, the threat of microplastics should also be taken into serious consideration [31]. The following regulations are important on the EU level [26,27 Conversion of solid fuel to gas is the main point of gasification [32,33].…”
Section: Of 14mentioning
confidence: 99%
“…This implies that most of the MPs removed during wastewater treatment will end up in the open environment [33,61]. For this reason, Wolff et al [62] indicated that WWTPs are a good sink for MPs only when the sludge is thermally treated and not used for agricultural amendment.…”
Section: Microplastic Accumulation In Sludgesmentioning
confidence: 99%